Effectiveness of bulking agents in managing stress and mixed urinary incontinence: a systematic review and meta-analysis - Alma Dhiani Paramita; Fiqih Faizara Ustadi; Jennifer Susanto; Moch. Afrizal Ansori; Eighty Mardiyan Kurniawati; Tri Hastono Setyo Hadi (Počki)
Stress urinary incontinence and stress-predominant mixed urinary incontinence are prevalent conditions that significantly impair quality of life, particularly among women. Urethral bulking agents have emerged as a non-surgical treatment option for patients who are hesitant to undergo surgical interventions. The aim of this systematic review and meta-analysis is to evaluate the efficacy and safety of various urethral bulking agents, specifically Bulkamid, Macroplastique, and Urolastic, in treating stress urinary incontinence and stress-predominant mixed urinary incontinence. The review encompasses 15 studies, including randomized controlled trials and cohort studies, with a total of 1,120 patients. The analysis focuses on cure and improvement rates, complications, and the risk of bias associated with the included studies. The findings indicate that bulking agents demonstrate cure and improvement rates ranging from 70 to 80 %, with a pooled average of 75 %. Subgroup analyses reveal cure rates of 76 % for Bulkamid, 73 % for Urolastic, and 77 % for Macroplastique. Despite significant statistical heterogeneity, particularly for Bulkamid and Urolastic, the results suggest that these agents can serve as effective non-surgical options. The outcomes appear consistent across all continents included in this study, reinforcing their potential as reliable alternative globally. However, the review highlights the necessity for well-designed randomized controlled trials to further assess the long-term efficacy and safety of these treatments, ultimately aiming to optimize patient outcomes.